Identifikasi Kegiatan Pramuka Dalam Mengembangkan Karakter Disiplin Siswa Di SD Negeri 01 Bolong Karanganyar - Azizah Ulfah, Istrina; , Dr. Achmad Fathoni, M.Pd (2017)
This research has purpose to 1) Identification scout activity which can develop discipline characters of students at SDN 1 Bolong Karanganyar, 2) Describing the obstacle of pramuka activity at SDN 1 Bolong Karanganyar. 3) Describing solution to cope the obstacle of pramuka activity at SDN 1 Bolong Karanganyar. This research used qualitative. Data collection techniques were used interviews, observation and documentation. Data validity of this research used triangulation. Data were analyzed interactively. The result of this research show that: 1) the activity of scout which can developing discipline character of students that is: a) ceremony developing discipline of rule and do positive activity with folllow ceremony. b) Learning Dasadarma and Trisatya developing dicipline of rule with responsible and do positive activity. c) Subject compass and establish tent aims to provide skills to strudents. d)PBB developing discipline of rule becaise concentrate carry out pembina instruction. 2) The obstacle of implementation of: a) activities pramuka the lack of coach personeel. b) The characteristics of students are still labile. c) Weather factors. 3) The solution of barriers activities pramuka namely: a)Change the schedule foster if have an interest suddenly. b) The pramuka punctuated played/ applause so that students interest following the activities. c) The activities proceed in the third and fourth grade if have a rain.